Adaptive text recognition algorithms - Isakhanov Khushnidbek Murodiljanovich , Tokhirova Sarvinoz Gayratjon Kizi (Miasto Przyszłości, 2024)
Adaptable the text determination algorithms different different the text information types and the environment conditions automatic respectively adapt will receive methods and models work exit with depends has been research is the field . This algorithms natural the language again performance (NLP) and the car learning in the field main are components . Adaptable the text determination of algorithms purpose hand writing automatic identify the signs optical recognition (OCR), text feeling analysis to make , information separate get the text classification and others such as different in applications the text information to determine accuracy and efficiency from raising consists of